Assessing willingness to pay for improved sanitation in rural Vietnam - Hoang Van Minh; Hung Nguyen-Viet; Nguyen Hoang Thanh; Jui-Chen Yang (Springer, 2013)
Objective: The willingness to pay (WTP) for the construction of bathrooms with a flush toilet was assessed in households in a rural community in northern Vietnam. We also examined the effects of socio-economic factors on the WTP. Methods: The contingent valuation method, an economic survey technique, was used. We used the iterative bidding game technique to elicit household WTP that involved a sequence of dichotomous choice questions followed by a final open-ended question. A total of 370 households that did not have toilets were selected for this study. Respondents to the questionnaire were the primary income earners and decision-makers of their respective household. Results: Of those responding to the questionnaire, 62.1 % reported being willing to pay for the construction of bathrooms with a flush toilet. The mean and median of maximum WTP amounts were Viet Nam Dong (VND) 15.6 million and VND 13.0 million, respectively (minimum VND 2.0 million; maximum VND 45.0 million). Significant correlates of the WTP rate were: (1) gender of the head of household, (2) age of the head of household, (3) economic status of household, (4) type of current toilet, (5) satisfaction with existing toilet, and (6) knowledge of health effects of poor sanitation. The significant determinants of WTP amount were (1) geographic location and (2) economic status of household. Conclusion: About two-third of the households in the study area were willing to pay for an improvement in their current sanitation arrangements. Both WTP rate and WP amount were strongly influenced by the economic status of the households and health knowledge of the study respondents.